Foreign Direct Investment, Portfolio Investment, and Economic Growth in Indonesia: Vector Auto Regression Approach - Ghazali Syamni (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
The goal of this research is to examine the Foreign Direct Investment (FDI), Portfolio Investment (PI) and Economic Growth (EG) correlation in Indonesia.  This research is using the Economic growth, foreign direct investment and portfolio investment data during 2010-2016, which is accessed from  www.bps.go.id; www.bkpm.go.id and www.bi.go.id, and using Vector Auto Regression method. The result shows that FDI and EG have two way correlationship, meaning the connection between  past Indonesia FDI and recent Indonesia EG are exist. PI and EG have the same correlationship yet it does not influence the investors to invest at the Indonesia Stock Exchange, as they, particularly foreign investors, are looking forward to the Indonesia Macro-economy policies or recent information about it.